2014
DOI: 10.21273/jashs.139.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Controlling Amounts and Types of Epicuticular Waxes in Onion

Abstract: Natural variation exists in onion (Allium cepa L.) for amounts and types of epicuticular waxes on leaves. Wild-type waxy onion possesses copious amounts of these waxes, whereas the foliage of semiglossy and glossy phenotypes accumulates significantly less wax. Reduced amounts of epicuticular waxes have been associated with resistance to onion thrips (Thrips tabaci Lindeman), an important insect pest of onion. A segregating family from the cross of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…). Glossy and semi‐glossy foliage has been shown to be non‐preference to thrips feeding damage in onion (Damon and Havey ). Genetic studies indicate low heritability for thrips resistance, and it would be desirable to use family based selection to increase genetic gain (Hamilton et al.…”
Section: Breeding Achievements and Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…). Glossy and semi‐glossy foliage has been shown to be non‐preference to thrips feeding damage in onion (Damon and Havey ). Genetic studies indicate low heritability for thrips resistance, and it would be desirable to use family based selection to increase genetic gain (Hamilton et al.…”
Section: Breeding Achievements and Challengesmentioning
confidence: 99%
“…In recent years, it has been observed that onion has natural variation for the amount and types of epicuticular waxes (Bag et al. , Damon and Havey ). Onion accessions with glossy or semi‐glossy foliage have lower wax content, which associated with non‐preference to onion thrips.…”
Section: Molecular Breeding In Onionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we used onion EST clones and sequences available from the NCBI database to develop DNA probes for in situ hybridization to onion chromosome 5. We focused on chromosome 5 because it carries major quantitative trait loci (QTL) of interest to breeders that control bulb dry-matter content, pungency and storability, leaf waxiness, and resistance to abiotic factors (McCallum et al 2007;Masamura et al 2012;Damon and Havey 2014). We describe a new approach of DNA probe development based on producing exon-intron containing genomic fragments using PCR with primers designed on known exon sequences.…”
Section: Introductionmentioning
confidence: 99%